A Memetic Algorithm for Logic Circuit Design - Reis, Cecília (2019)
Memetic Algorithms (MAs) have shown to be very effective in solving many hard combinatorial optimization problems. In this perspective, this paper presents a MA for combinational logic circuits synthesis. The proposed MA combines a Genetic Algorithm (GA) for digital circuit design with the gate type local search (GTLS). The combination of a global and a local search is a strategy used by many successful hybrid optimization approaches. The main idea is to apply a local refinement to an Evolutionary Algorithm (EA) in order to improve the fitness of the individuals in the population. The obtained results indicate that the MA reduces the number of generations required to reach the solutions and its standard deviation while improves the final fitness function.